Household Food Security Status, Food Purchasing, and Nutritional Health of Saudi Girls Aged 6-12 Years - Mumena, Walaa, A; Kutbi, Hebah, A (Progress in Nutrition, 2021)
Background/Aim: To assess the prevalence of food insecurity at the household level and to investigate its relationship with anthropometric measurements, dietary intake, and frequency of food purchasing among Saudi girls.Material and Methods: This cross-sectional study included 119 girls aged 6-12 years and their mothers who were recruited from four public schools in Madinah, Saudi Arabia. Sociodemographic data, anthropometric measurements (height and weight) for both mothers and girls, dietary intake of girls (energy-adjusted nutrient intake calculated from single 24-hr dietary recall), and frequency of household food purchasing were evaluated. The Food Insecurity Experience Scale was utilized to evaluate the food security status. Results: Nearly one-quarter of the participants were experiencing food insecurity, wherein fathers education level, household income, and household crowding were negatively associated with food security status (p< .05). Household food security status was not linked to weight status or height of girls. However, food security status was positively associated with energy-adjusted vitamin D intake (B= 2.02 (SE= 0.86), [95% CI 0.31 to 3.72], p= .021). Additionally, significantly lower frequencies of purchasing fruits and vegetables, milk and dairy products, and meat were observed among food insecure households compared to food secure households (p< .05).Conclusion: The high prevalence of food insecurity observed among our sample is concerning. Household food insecurity was linked to lower vitamin D intake among Saudi girls as well as lower purchasing of healthy foods. Interventions are needed to increase the accessibility of healthy food options among children experiencing food insecurity.